Research design qualitative, quantitative, and mixed methods approaches - Creswell, John W.; Creswell, J. David (SAGE, 2018)
"The Fifth Edition includes more coverage of: epistemological and ontological positioning in relation to the research question and chosen methodology; case study, PAR, visual and online methods in qualitative research; qualitative and quantitative data analysis software; and in quantitative methods more on power analysis to determine sample size, and more coverage of experimental and survey designs; and updated with the latest thinking and research in mixed methods"--Provided by publisher.